“They seemed to forget about us little people”: the lived experiences of personal care attendants during the COVID-19 pandemic - Wendel, Carrie; Sullivan, Darcy L.; Babitzke, Jennifer; La Pierre, Tracey A. (Frontiers in Sociology, 2025)
BackgroundPersonal care attendants (PCAs) provided essential care and support to home care clients during the COVID-19 pandemic and thus were a vital part of the pandemic response in helping to keep older adults and individuals with disabilities out of nursing homes. Furthermore, they are one of the largest and fastest growing workforces in the United States. Yet this essential workforce received little attention during the pandemic. Guided by feminist theories on caregiving and the principles of community-based participatory research, this study examined the experiences of PCAs during the COVID-19 pandemic.MethodsData from 78 in-depth interview participants representing Medicaid-Funded Home and Community-Based Services (HCBS) PCAs, clients, family caregivers, and service providers in Kansas, United States, as well as additional data from 176 PCA survey participants were analyzed. Findings from this interactive, convergent, mixed-methods study were integrated by theme using the weaving approach.ResultsFour major themes emerged from the analysis: (1) PCAs remained in this field during the pandemic out of a commitment to their clients; (2) PCAs were undervalued and invisible as an essential workforce; (3) direct care work had an emotional toll on PCAs during the pandemic; and (4) PCAs have mixed feelings about their satisfaction with the job, and, as good workers quit, they were difficult to replace.DiscussionPCAs held professional-level responsibilities without the recognition or pay of a professional. The pandemic had mixed impacts on job stress and satisfaction, suggesting that the intrinsic rewards of the job and social support had a protective impact. However, intrinsic rewards are not enough to retain this workforce, and the growing PCA workforce shortage leaves many clients having to choose between no care and poor care. Our findings indicate that institutions and systems must better support and recognize this essential workforce to build and maintain a quality in-home care services system.